2013
DOI: 10.1519/jsc.0b013e3182606e05
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes of Jumping Performance and Knee Muscle Strength in Under-19 Women Volleyball Players

Abstract: The purpose of the study was to compare the seasonal changes (preparation period [PP] and competition period [CP]) of vertical jumping performance and knee muscle strength in a team of under-19 women volleyball players (N = 12, 16.2 ± 1.5 years). The countermovement jump was used to evaluate jumping performance. The isometric knee extension moment at 150 ms from the onset of contraction (T150) and at a maximum of contraction (TMAX) were determined at 9 knee angles (from 10° to 90°, full knee extension = 0°). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
1
18
0
4
Order By: Relevance
“…For this reason, improvements in the vertical jump and explosive power can be associated with jumping movements in the trainings rather than play. Regarding this, Vilamitjana (30), Marques (23) Gonzalez (6) and Rousanoglou (29) reported that there was a significant increase in the volleyball players' jump height and explosive power, thanks to the applied specific training. However, Hakkinen (7) and Newton (25) pointed out that if no specific training was applied, vertical jump height of the volleyball players would be significantly decrease in relation to the length of the competition period.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, improvements in the vertical jump and explosive power can be associated with jumping movements in the trainings rather than play. Regarding this, Vilamitjana (30), Marques (23) Gonzalez (6) and Rousanoglou (29) reported that there was a significant increase in the volleyball players' jump height and explosive power, thanks to the applied specific training. However, Hakkinen (7) and Newton (25) pointed out that if no specific training was applied, vertical jump height of the volleyball players would be significantly decrease in relation to the length of the competition period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the importance of muscular strength profiles to evaluate injury risk, the ability to produce high levels of strength is an important contributor to explosive sports, which rely heavily on the capacity to move one's own body mass (ie, acceleration, change of direction, etc) or that of an object (ball, discus, loaded barbell). Considering the importance of knowing about athletic muscular strength, researchers have highlighted the importance of verifying the effect of a sports season on isokinetic muscular strength in various sports and joints .…”
Section: Introductionmentioning
confidence: 99%
“…Esto se debe, en gran parte, a que las técnicas de estiramiento utilizadas con el rodillo de espuma y de facilitación neuromuscular propioceptiva mejoran el ciclo de estiramiento -acortamiento, activando el reflejo miotático, lo cual ayuda a aprovechar la energía elástica, es decir, la capacidad que tiene el músculo para almacenar energía durante el estiramiento y utilizarla en una posterior contracción o acción de potencia (Belmonte-Férez, 2015). Por esta razón, los valores de la RMS disminuyeron después de la intervención, ya que los músculos isquiosurales necesitaron una menor activación para generar una actividad explosiva, aumentando la potencia media de los músculos involucrados en el salto vertical sin ocasionar un mayor gasto energético (Rousanoglou, et al, 2013).…”
Section: Discussionunclassified